Estimation of Energy and Protein Requirements of Arabic Hens during Rearing Period by Free Choice Feeding - Syafwan; Noferdiman; S. Zubaida; T. M. Pasaribu; Adrizal (Faculty of Animal Science, Bogor Agricultural University, 2021)
The present experiment was conducted to estimate the metabolizable energy (ME) and crude protein (CP) requirements of female Arabic chickens under a semi-scavenging system from starter to first egg-laying age. Two hundred and forty-five day-old chicks were allotted into 12 sheltered pens with 20 chicks each. They were offered either control or choice diet and replicated six times. The control group was offered a control diet based on the Hy-line Brown Nutrient Requirements Standard, whereas the choice group was offered a control diet (starter period: 2910 kcal of ME/kg and 19.7% of CP; grower period: 2854 kcal of ME/kg and 17.5% of CP; developer period: 2754 kcal of ME/kg and 16.0% of CP; pre-laying period: 2776 kcal of ME/kg and 16.5% of CP; and laying period: 2814 kcal of ME/kg and 18.4% of CP) together with four other diets (high energy-high protein [3101 kcal of ME/kg and 23.0% of CP], high energy-low protein [3133 kcal of ME/kg and 14.3% of CP, low energy-high protein [2638 kcal of ME/kg and 23.4% of CP], and low energy-low protein [2677 kcal of ME/kg and 14.6% of CP]). Data were analyzed using Proc Mixed of SAS. Results showed that feed intake was significantly lower in choice dietary treatments in all periods, except in the starter period. ME and CP intakes were similar (p>0.05) in all periods. However, ME and CP concentrations in the diet consumed were higher (p<0.05) in choice dietary treatment in all periods, except CP concentration in the starter period. BWG started to be higher (p<0.05) in choice dietary treatment during the developer and pre-laying period. The onset of laying was two days early in choice-fed birds. It can be concluded that free choice feeding on a diet varying in energy and protein had a beneficial effect on the growth rate of female Arabic hens by consuming more a high energy-high protein and a high energy-low protein diet. ME and CP requirements of Arabic hens for starter period were 3026 kcal of ME/kg and 18.8%, for grower period were 3081 kcal of ME/kg and 18.4%, for developer period were 3091 kcal of ME/kg and 18.5%, and for pre-laying period were 3072 kcal of ME/kg and 18.8% to faster the onset of laying.